2023
DOI: 10.3389/fpsyg.2023.1120238
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of personality differences of Polish mountaineers

Abstract: A noticeably increased interest in mountain climbing, both as the form of extreme sport and a form of tourism, has been observed in Poland recently. The assumption of this study is that practicing different varieties of mountaineering influences the personality of Polish climbers in a different manner. The aim of the research was to compare the personality differences of Polish mountaineers. To this aim, the population of Polish high-performance mountaineers was studied (N = 81; including 39 women and 42 men).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Different research supports these results, where resilient athletes who are more satisfied with life predict positively and significantly higher EI [47]. In relation to these aspects, several elements coexist that connect resilience and life satisfaction, such as health, sports performance and context, as well as the emotions experienced in personal activities and relationships [3,[21][22][23], so that athletes who show higher personal competences also show higher life satisfaction, where resilience plays a mediating role with EI [47,73].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Different research supports these results, where resilient athletes who are more satisfied with life predict positively and significantly higher EI [47]. In relation to these aspects, several elements coexist that connect resilience and life satisfaction, such as health, sports performance and context, as well as the emotions experienced in personal activities and relationships [3,[21][22][23], so that athletes who show higher personal competences also show higher life satisfaction, where resilience plays a mediating role with EI [47,73].…”
Section: Discussionmentioning
confidence: 96%
“…Resilience develops from personal growth in adverse circumstances [71]. In the field of sport, within a framework of reference for the promotion of personal growth in high-level sporting disciplines, intrapersonal resilient resources should be considered as they are beneficial in sporting activities with a high level of self-improvement and athlete psychological well-being [69,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, personality traits were found to have a predictive effect on physical education class satisfaction, consistent with prior research such as the studies conducted by Baruth and Cohen (2023) and Shih et al (2014) , which demonstrated that personality traits can predict satisfaction in online learning courses among college students. Numerous studies have demonstrated that personality traits are significant factors influencing physical activities ( Burgos-Garrido et al, 2011 ; Wilson et al, 2016 ; Engels et al, 2022 ; Piepiora et al, 2023 ), and they can serve as indicators for predicting sports engagement ( Smith et al, 2017 ) and performance ( Piepiora, 2021 ). The research by Piepiora corroborates the relationship between sports and personality traits: as the duration of physical activities increases, so do the scores on the Big Five personality traits ( Piepiora et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%